Workload Analysis in Pharmacy Installation Regional General Hospital X as a Basis for Planning Pharmacy Personnel Needs and Pharmacy Service Quality - Nurfajri, Nurfajri; Sahat Saragi; Lies Putriana (Sean Institute, 2025)
Improvement burden Work power pharmacy can impact to quality service pharmacy If No balanced with amount power appropriate pharmacy . Determine amount the power that in accordance with burden Work can done with do analysis burden work in the existing unit complaints . Complaints can originate from power pharmacy and from patient . Complaints is problems that must be overcome Because can influence quality service pharmacy to patients . In the Pharmacy Installation of RSUD X there are a number of complaint from power pharmacy related burden perceived work Enough height and complaints from patient related time Wait drug so that need done analysis burden work in the unit For know description burden impactful work to quality service pharmacy as well as amount power appropriate pharmacy with burden existing work moment this . Research This use method quantitative descriptive with technique data collection through observation all over activity power pharmacy use method work sampling For count amount need power pharmacy as well as use questionnaire satisfaction customer to patient For know description quality service . Result data observation in analysis use Workload Indicators of Staffing Need (WISN) and for results questionnaire analyzed use S ERVQUAL method . Workload and quality service connected use linear regression for see influence burden Work to quality service . From the results study show that amount need power pharmacy at RSUD X is 4,684 people and obtained ratio of 1.07 which means that power pharmacy considered overstaffing Because ratio >1. Meanwhile For quality services received from results questionnaire Then analyzed use method SERVQUAL state that there is difference between reality and hope Where patient Still want better service Good from what exists moment This is for know influence burden Work moment This to quality service analyzed use linear regression and its results is 46.3% which means that quality service is affected by load Work by 46.3%.